Analysis of seven STR human loci for paternity testing by microchip electrophoresis - Fraige,Karina (2013)
The aim of this work was to evaluate two paternity cases by microchip electrophoresis and the validation of the methodology by comparison of the results with those obtained in a commercial genetic analyzer. It was observed that when working with tetranucleotide regions, in which the minimal difference between the alleles was only four base pairs, the commercial microchip system did not present the resolution and repeatability needed. Nevertheless, the relative standard deviation was between 0 and 1.2% and the fragments detected were within the expected size ranges as described in the literature.